DIDACTIC CONDITIONS OF USE OF COMPUTER EDUCATIONAL MATERIALS FOR THE DEVELOPMENT OF AESTHETIC EVALUATION RURAL ADOLESCENTS (Pedagogy of Higher and Secondary Education, 2022)
The issues of the day of development of aesthetic estimation of teenagers of nal bcality are examined in the articl, provodidtsya analysis of crisis position of problem of teaching of teenagers of rural locality to aesthetic taste, a structure of aesthetic estimstion and didaditicheskie condiion of the use is computer techonologists of teaching aesthetic taste.
Keywords: structure of aesthetic estimation; aesthetic taste; aesthetic consciousness; computer technology of teaching of aesthetic taste